Evaluation of the environmental sustainability of agricultural production using the methodologies of emergy analysis and life cycle assessment. Case study, tomato grown in Mendoza (Argentina) - Piastrellini, Roxana; Rotolo, Gloria Claudia; Arena, Alejandro Pablo; Civit, Bárbara María; Curadelli, Silvia (Elsevier, 2024)
This article evaluates the environmental performance of tomato production in Mendoza (Argentina) using two methodologies that share the same approach and part of the inventory: i) Life Cycle Analysis, a method that considers all flows (incoming and outgoing) involved in the life cycle of a product, and ii) Emergetic Analysis, which represents the environmental support provided directly and indirectly by the biosphere to economic processes in the form of resources and ecosystem services. The combined application of these two tools helps to identify critical points in the production system and to generate proposals for improvement and innovation. In this case, the critical points identified are irrigation and fertilizers. Specifically for the environmental category Climate change, crop irrigation represents 51 % of the total impact, while seedling production represents 22 %. The emergy analysis, without accounting for direct and indirect human labor, shows a low contribution of local natural resources to the final product (0.12 %), as well as an environmental burden of 7.23 %. The results show that the local environmental dynamics are altered because tomato production is mostly driven by external inputs, mainly fertilizers (especially nitrogenous fertilizers) and energy.